Effects of isometric loading intensity on patellar tendon microvascular response. (8th May 2022) - Earp, Jacob E.; Gesick, Haley; Angelino, Domenic; Adami, Alessandra
Abstract : Acute increases in tendon blood flow and oxygenation after stress (i.e., hyperemic response) can enhance tendon recovery. While loading intensity is a fundamental part of resistance training programs, its effects on tendon's hyperemic response are unknown. This study aimed to compare acute changes in total (total hemoglobin [THb]) and oxygenated hemoglobin (HbO2 ) concentrations in the patellar tendon after isometric exercise at different intensities. Thirteen participants performed 8 (5 s) isometric knee extensions at 25%, 50%, and 75% maximal load (maximal voluntarily isometric contraction [MVIC]), separated by 20 min recovery, prescribed in randomized and counterbalanced order. Changes in patellar tendon THb, HbO2 and deoxygenated hemoglobin (HHb) in response to exercise at each intensity were measured using near‐infrared spectroscopy. Post‐exercise, HbO2 increased with 50% ( η p 2 = 0.305, f = 5.26, p < 0.01) and 75% ( η p 2 = 0.245, f = 4.56, p < 0.01) but not 25% ( η p 2 = 0.088, f = 1.16, p = 0.339) MVIC, while THb increased in 50% ( η p 2 = 0.305, f = 5.26, p = 0.01) but not 25% ( η p 2 = 0.067, f = 0.865, p = 0.51) or 75% ( η p 2 = 0.126, f = 1.729, p = 0.14) MVIC. Additionally, increasing load from 25% to 50% MVIC resulted in greater THb ( f = 2.459, p = 0.43), HbO2 ( f = 3.389, p = 0.13) and HHb ( f = 0.320, p = 0.01) post‐exercise responses, but no differences were observed between 50% and 75% MVIC (THb: f = 0.748, p = 0.59; HbO2 : f = 0.825, p = 0.54; HHb: f = 0.713, p = 0.62). Our results suggest there is a loading threshold at 50% MVIC at which the tendon hyperemic response is fully achieved. Training above this intensity is not expected to provide any additional change to the tendon microvascular response. Therefore, moderate loading seems to be sufficient to fully elicit the patellar tendon hyperemic response that's believed to stimulate tendon healing.